Research Progress of Lateral Flow Immunoassay in Food Safety - Lingzhi YAN (Shipin gongye ke-ji, 2022)
lateral flow immunoassay (LFIA) not only effectively combines the separation ability of chromatography technology and the excellent specificity of immunoassay methods, but also provides an ideal platform for the on-site detection of food safety with advantages of easy operation, rapid detection and low cost. Gold nanoparticle is a commonly used signal label in the field of LFIA analysis. Unfortunately, conventional gold-based LFIA often suffers from drawbacks of low sensitivity, which can only satisfy qualitative and semi-quantitative information on analyte concentrations. To improve the detection performance of LFIA, researchers have made significant efforts. In this contribution, the basic principle of LFIA is introduced and the recent technical improvements are systematically summarized, such as developing novel signal nanoparticles, signal enhancement method, multiplex target detection and different signal readout mode, etc. Meanwhile, this study discusses the shortcomings and the trend of LFIA, which would provide technical references for the development of rapid detection methods for food safety in China.